Error analysis in writing: a comparative study of Bangla medium and English medium schools in Dhaka - Sayeed, Ireen (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Applied Linguistics and ELT, 2016.